The "new" environmental policy of the European Union: A path to development of a circular economy and mitigation of the negative effects of climate change - Zofia Wysokińska (Comparative Economic Research. Central and Eastern Europe, 2016)
This paper analyses the evolution of the new environmental policy of the European Union in the context of the efforts undertaken to moderate the negative effects of climate change. It describes all the activities in the European Union designed to implement new tools of the EU environmental policy, such as low carbon economy technologies, tools that improve the efficiency of managing the limited natural resources, the environmentally friendly transport package, etc. All of them are aimed at laying the foundations of the circular economy, which may also be referred to as a closed-loop economy, i.e., an economy that does not generate excessive waste and whereby any waste becomes a resource.
Keywords: 330; EU's new environmental policy; climate change; circular economy